Influence of Knowledge and Attitude of Trimester Pregnant Women with Breast Milk Feeding at the Health Center - Sabriana, Riska; Raehan, Raehan; Suria Saputri, Nurul Aini; Mahendika, Devin; Surya, Sara; Supriatin, Supriatin; Mustari, Sahdan (International Journal of Health Sciences, 2023)
Exclusive breastfeeding is the provision of breast milk to infants only for 6 months, namely from 0-6 months, without the addition of other liquids such as formula, orange, honey, tea, and water, and without additional solid foods such as bananas, milk porridge, biscuits, rice porridge, and team rice. The purpose of this study was to determine the relationship between knowledge and attitudes of third trimester pregnant women with exclusive breastfeeding at the Puskesmas. This research is a type of surveianalytic research, with a cross sectional stady approach. The population in this study was 130 people with a sample size of 33 people who were taken using the Slovin formula with purposive sampling technique. Data analysis techniques used are univariate analysis and bivariate analysis. Through research, the results of univariate analysis were obtained, namely good knowledge (63.63%), unfavorable attitudes (57.57%), and those who provide exclusive breastfeeding (54.54%) and bivariate analysis, namely knowledge with the Chi-Square statistical test obtained x2count 0.1 and x2table 3.841 so that x2count < x2table then H0 is accepted and Ha is rejected, the mother's attitude obtained x2count 0.05 and x2table 3.841 so x2count < x2table then H0 is accepted and Ha is rejected. Based on the research, it can be concluded that there is no relationship between knowledge and attitude of third trimester pregnant women. For health centers, to routinely conduct counseling about exclusive breastfeeding, and explain the benefits of exclusive breastfeeding both for mothers and for babies.